Konservasi Wilayah Recharge Daerah Air Tanah Dan Wilayah Pelepasan Berbasis Doyo Baru Jayapura - Theodora Ngaderman; Anna Rumabar; Marthina Mini; Mercy Zebua (Peneliti.net, 2023)
Factors that influence groundwater conservation include; groundwater basin boundaries, recharge areas and groundwater discharge areas, as well as water sources. The methods used in this research are interviews and questionnaires, measurement and observation. The geology of the research area consists of the oldest lithology, namely metamorphic rocks, then fluvial deposits were deposited on top. Geomorphologically, it is composed of structural hill and fluvial plain morphological units. Doyo Baru is located in the Sentani groundwater basin system (CAT), with rock formations that are fluvial deposits where water sources are known to be abundant. The groundwater basin (CAT) in the Jayapura region shows low water sources in rock formations of Tertiary Miocene age. Meanwhile, the groundwater basin of the Demta rock formation, which makes up Pre-Tertiary age metamorphic (pTMc) and ultramafic (UM) rock units, is known to have moderate water sources. The recharge area in the Doyo Baru area is visible on the map in blue, while the area in white is the discharge area. The discharge area here is also the Doyo Baru groundwater basin (CAT). The catchment area from the spring is shown on the map, while the depth of the groundwater level is measured in community wells on the map which is circled in red. The catchment area from the spring is shown on the map, while the depth of the groundwater level is measured in community wells on the map which is circled in red. Conservation areas appear on the map of the Doyo Baru area in blue where existing water sources need to be protected and preserved. Wells made in disposal areas generally have shallow groundwater depth. From the measurement results, the Doyo Baru research area is at an altitude of 84-108 m above sea level with a groundwater level ranging from 8-28 m (below the CAT surface).